Laser-induced breakdown spectroscopy: Extending its application to soil pH measurements - Ferreira, Edilene Cristina [UNESP]; Gomes Neto, José A. [UNESP]; Milori, Débora M.B.P.; Ferreira, Ednaldo José; Anzano, Jesús Manuel (Elsevier, 2015)
Acid-base equilibria are involved in almost all the processes that occur in soil. The bioavailability of nutrients for plants, for instance, depends on the solubilization of mineral nutrients in the soil solution, which is a pH-dependent process. The determination of pH in soil solutions is usually carried out by potentiometry using a glass membrane electrode, after extracting some of the soil components with water or CaCl2 solution. The present work describes a simple method for determining the pH of soil, using laser-induced breakdown spectroscopy (LIBS). Sixty samples presenting different textural composition and pH (previously determined by potentiometry) were employed. The samples were divided into a calibration set with fifty samples and a validation set with ten samples. LIBS spectra were recorded for each pelleted sample using laser pulse energy of 115 mJ. The intensities of thirty-two emission lines for Al, Ca, H, and O were used to fit a partial least squares (PLS) model. The model was validated by prediction of the pH of the validation set samples, which showed good agreement with the reference values. The prediction mean absolute error was 0.3 pH units and the root mean square error of the prediction was 0.4. These results highlight the potential of LIBS for use in other applications beyond elemental composition determinations. For soil analysis, the proposed method offers the possibility of determining pH, in addition to nutrients and contaminants, using a single LIBS measurement.
Keywords: LIBS; PLS; Soil pH determination